Azimuth Angle and Magnetic Declination to Maximize Solar Panel Efficiency (Solar Tracking System) - Saeed, Zubair; Shahzad, Waseem; Ur Rehman, Asad; Ali, Syeda Zuriat e Zehra; Zaman, Shah; Shehzad, Faheem (Department of Electrical Engineering ITS and FORTEI, 2024)
This study presents the idea of power production through the solar which depends on the light intensity that falls on the solar panel. This project utilizes dual axis solar tracking system based on intensity of light using Arduino UNO. The hardware implementation includes an Arduino UNO and four LDR sensor for sensing the maximum intensity of light. Two DC motors are used, one motor is used for horizontal rotation and the second motor is used for the vertical rotation. This system includes the implementation of MPPT. It controls the charge and stores it in a battery. Battery provides 12V to inverter where DC voltages convert into AC voltages. SPWM inverter is designed over push pull topology. In conclusion, the proposed system operates on low input power and delivers high efficiency in output.